Reconstitution of the membrane protein OmpF into biomimetic block copolymer–phospholipid hybrid membranes - Bieligmeyer, Matthias; Artukovic, Franjo; Nussberger, Stephan; Hirth, Thomas; Schiestel, Thomas; Müller, Michaela (Beilstein Journal of Nanotechnology, 2016)
Structure and function of many transmembrane proteins are affected by their environment. In this respect, reconstitution of a membrane protein into a biomimetic polymer membrane can alter its function. To overcome this problem we used membranes formed by poly(1,4-isoprene-block-ethylene oxide) block copolymers blended with 1,2-diphytanoyl-sn-glycero-3-phosphocholine. By reconstituting the outer membrane protein OmpF from Escherichia coli into these membranes, we demonstrate functionality of this protein in biomimetic lipopolymer membranes, independent of the molecular weight of the block copolymers. At low voltages, the channel conductance of OmpF in 1 M KCl was around 2.3 nS. In line with these experiments, integration of OmpF was also revealed by impedance spectroscopy. Our results indicate that blending synthetic polymer membranes with phospholipids allows for the reconstitution of transmembrane proteins under preservation of protein function, independent of the membrane thickness.
Keywords: biomimetics; block copolymer; lipopolymer mixture; OmpF reconstitution; self-assembly